Early perception of stink bug damage in developing seeds of field-grown soybean induces chemical defences and reduces bug attack - Giacometti, Romina (2015)
BACKGROUND: Southern green stink bugs (Nezara viridula L.) invade field‐grown soybean crops, where they feed on developing seeds and inject phytotoxic saliva, which causes yield reduction. Although leaf responses to herbivory are well studied, no information is available about the regulation of defences in seeds. RESULTS: This study demonstrated that mitogen‐activated protein kinases MPK3, MPK4 and MPK6 are expressed and activated in developing seeds of field‐grown soybean and regulate a defensive response after stink bug damage. Although 10–20 min after stink bug feeding on seeds induced the expression of MPK3, MPK6 and MPK4, only MPK6 was phosphorylated after damage. Herbivory induced an early peak of jasmonic acid (JA) accumulation and ethylene (ET) emission after 3 h in developing seeds, whereas salicylic acid (SA) was also induced early, and at increasing levels up to 72 h after damage. Damaged seeds upregulated defensive genes typically modulated by JA/ET or SA, which in turn reduced the activity of digestive enzymes in the gut of stink bugs. Induced seeds were less preferred by stink bugs. CONCLUSION: This study shows that stink bug damage induces seed defences, which is perceived early by MPKs that may activate defence metabolic pathways in developing seeds of field‐grown soybean.